The price trend and their impact on profit margin and safety of the protein for feed in Romania - Gheorghe Adrian Zugravu; Maria Magdalena Turek Rahoveanu; Liliana Mihaela Moga; Mihaela Neculita (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Because modern sophistication in the trade, transport, handling, blending and distribution system that makes the feed to reach farmers in the formula "just in time" protein sources are now in difficulty. The paper follows two main objectives: to understand farmers' perception of safety and quality of protein for stockbreeding and to identify communication levers in order to improve the protein self-sufficiency for animal production. This paper conducted a questionnaire survey of Romanian farmers' perception toward safety and quality of protein for feed. The empirical study with brands indicated that farmers are different awareness to safety and quality of protein for feed.
Keywords: 330; safety perception; feed quality; protein self-sufficiency